What Do Healthcare Providers Advise Women with Multiple Sclerosis Regarding Pregnancy?. (5th March 2014) - Wundes, Annette; Pebdani, Roxanna N.; Amtmann, Dagmar
Abstract : Pregnancy in multiple sclerosis (MS) is considered safe for both the woman and the child. Nevertheless, pregnancy issues in MS are complex both from a patient's and a provider's perspective. In an anonymous survey, 28 healthcare providers in the United States reported on the management of multiple sclerosis (MS) during pregnancy. Participants were asked about their recommendations to patients about the use of disease modifying therapies during pregnancy and breastfeeding and general recommendations about MS and pregnancy. Healthcare providers were also asked about sources from which they receive information about the management of patients with MS. Results suggested that healthcare providers do not discourage pregnancy for women with MS, recommend that women not use disease modifying therapies while pregnant, and have a positive view of breastfeeding for women with MS. Results also indicated the need for guidelines on patient management for pregnant women with MS.